Diverse grouping and mating strategies in the Critically Endangered Hainan gibbon (Nomascus hainanus) - Ping Li; Paul A. Garber; Yu Bi; Kun Jin; Xuming Qi; Jiang Zhou (Primates, 2022)
Understanding flexibility in the social structure and mating strategies of the world’s last remaining population (35 individuals) of wild Hainan gibbons ( Nomascus hainanus ) is critical for developing effective management plans to aid in their population recovery. Three of the five remaining Hainan gibbon groups (A, B, and C) currently live in a social unit characterized by two or three adult males, two reproducing adult females, and offspring. A fourth group (D) contains one adult male, two adult females, and offspring, and Group E contains a single adult male–adult female pair with a young infant. In this study, we describe observations of copulations between multiple resident males and one of the two resident females in Group C. Group C is best described as a small multi-male/multi-female group. We found that this breeding female (F2) solicited copulations from two resident adult males (M1 and M2) on the same day, and also mated with each of these two males on different days. Resident males were not observed to interrupt the mating pair. Although factors such as a biased adult sex ratio, severe population disruption, and habitat degradation can help explain variation in group composition and mating strategies in Hainan gibbons, we argue that there exists considerable mating system variability across gibbon species, and that this variability offers important insights into male and female Hainan gibbon group structure and reproductive strategies.